The international circulation of elites: Knowledge, entrepreneurial and political - Andrés Solimano; Diego Avanzini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
International migration analysis often focuses on mass migration rather than on the international mobility of elites, which is the focus of this paper. The paper offers a three-fold classification of elites: (a) knowledge elites, (b) entrepreneurial elites and (c) political elites. We explore the concept of elites and their main motivation to move across nations and review indirect empirical evidence relevant to this type of mobility, highlighting some channels through which elites can affect international development.
Keywords: F22; J61; L26; O15; 330; International migration; entrepreneurial; political migrants; talent mobility